THE PEDAGOGICAL EFFECTIVENESS OF USING ARTIFICIAL INTELLIGENCE TOOLS IN PRESCHOOL EDUCATION ORGANIZATIONS: OPPORTUNITIES AND CHALLENGES - Shomirzayeva Jumagul (International Journal of Literature and Language Studies, 2026)
This article analyzes the pedagogical effectiveness of using artificial intelligence (AI) tools in preschool education organizations, its impact on the educational process, and the existing opportunities and challenges. Modern digital technologies, particularly AI-based educational platforms, interactive programs, speech recognition systems, and adaptive learning applications, serve as essential tools in enhancing children's cognitive activity, supporting individual development, and improving the quality of education. Artificial intelligence enables educators to rapidly analyze children's knowledge levels and developmental characteristics, implement individualized approaches, and plan educational activities effectively. At the same time, these technologies contribute to developing independent thinking, creativity, and communication skills in children. However, the integration of artificial intelligence into the preschool education system also poses several challenges. In particular, the insufficient digital competence of educators, limited technical infrastructure, information security and data privacy concerns, as well as the risk of children becoming overly dependent on digital devices, are highlighted as pressing issues. Therefore, ensuring pedagogical appropriateness, considering age-specific characteristics, and harmonizing these technologies with traditional upbringing methods are of great importance when utilizing artificial intelligence tools. The research findings indicate that the rational use of artificial intelligence tools enhances the quality and efficiency of preschool education, while fostering children's intellectual and creative potential.